Hepatic Injury in Neonates with Perinatal Asphyxia - Akram Elshafey Elsadek MD; Naglaa FathyBarseem MD; Hany Abdelaziz Suliman MD; Hatem Hamed Elshorbagy MD; Naglaa M. Kamal MD; Iman M. Talaat MD; Ashraf Hamed Al-shokary MD; Yehia Hamed Abdel Maksoud MD; Asmaa Obada Ibrahim MD; Ahmed Mahmoud Attia; Waleed Abdellateef Abdelhalim MD; Waleed Elsayed Abdelghani MD (SAGE Publishing, 2021)
Background: Perinatal asphyxia (PA) is a major cause of morbidity and mortality in which dramatic transient impairment in liver functions occurs in some patients. Objectives: We aimed to evaluate the state of the liver in cases of Perinatal asphyxia and to assess the severity of hepatic impairment in relation to different grades of HIE. Patients and Methods: This case-control study was conducted on 100 full-term newborns with perinatal asphyxia (Group I) and 50 healthy neonates served as controls (Group II). All biochemical parameters of liver function were measured on the 1st, 3rd, and 10th day after birth. These parameters include serum alanine transferase (ALT), aspartate transferase (AST), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), total protein, serum albumin, serum bilirubin (total and direct), and international normalized ratio (INR), in both cases and controls. Results: Among babies with PA, 25 (25%) had an Apgar score of 0 to 3 (severe PA), 43 (43%) had an Apgar score of 4 to 5 (moderate PA) and 32 (32%) had an Apgar score of 6 to 7 (mild PA) at 5 minutes of life. HIE was found in 39% among cases of PA and the remaining 61% were normal. Among babies with PA and HIE; 25.7% had stage I, 41% had stage II and 33.3% had stage III. Impaired liver function was reported in 48% of asphyxiated babies. On the first day of life, ALT, AST, ALP, LDH, PT, and INR were significantly higher in Group I compared to Group II. However, total protein and serum albumin were significantly lower in Group I compared to Group II. ALT and AST showed a positive correlation with the severity of HIE. On the third day of life, LDH rises as the stage of HIE progressed from stage 0 to stage 3. The difference in LDH among most stages of HIE was statistically significant. Conclusion: Liver enzymes can be used as an easy early diagnostic marker to differentiate between babies with asphyxia and those without asphyxia. Also, liver enzymes can be used for the detection of the severity of PA.